Activation of innate immunity by Bordetella pertussis - Higgins, Sarah (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2005)
Respiratory infection with Bordetella pertussis is associated with the induction of Th1 cells and these cells, as well as antibody and cells of the innate immune system mediate the clearance of bacteria from the lungs. Signalling through toll-like receptors (TLR) activates dendritic cell (DC) maturation and IL-12 production, which directs the induction of Th1 cells. In contrast, DC activated by other pathogen-derived molecules such as B. pertussis filamentous hemagglutinin and adenylate cyclase toxin enhance TLR ligand induced IL-10 production, which in turn, promotes the induction of type 1 regulatory T (Tr1) cells. This study found that the production of IL-10, in addition to inflammatory cytokines and chemokines, was significantly reduced in DC from TLR4-defective mice in response to B. pertussis. TLR4 was also required for B. pertussis LPS-induced maturation of DC, but other B. pertussis components stimulated DC maturation independently of TLR4. The course of B. pertussis infection was more severe in TLR4-defective, C3H/HeJ mice compared with C3H/HeN mice. Surprisingly, antibody and antigen-specific IFN-y responses were enhanced at the peak of infection, whereas antigen-specific IL-10-producing T cells were significantly reduced in C3H/HeJ mice. This was associated with enhanced inflammatory cytokine production, cellular infiltration, and severe pathological changes in the lungs of TLR4- defective mice. These findings suggest that TLR4-mediated signalling activates innate IL-10 production in response to B. pertussis and promotes the induction of IL-10 secreting Tr1 cells. These Tr1 cells inhibit Th1 responses and limit inflammatory pathology in the lungs during infection with B. pertussis.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin